cheA, cheB, cheR, cheV, and cheY Are Involved in Regulating the Adhesion of Vibrio harveyi - Xu, Xiaojin; Li, Huiyao; Qi, Xin; Chen, Yunong; Qin, Yingxue; Zheng, Jiang; Jiang, Xinglong (Frontiers in Cellular and Infection Microbiology, 2021)
Diseases caused by Vibrio harveyi lead to severe economic losses in the aquaculture industry. Adhesion is an important disease-causing factor observed in bacteria with chemotactic activity. In our study, we measured V. harveyi chemotaxis by subjecting the bacteria to stress using Cu2+ (50 mg/L), Pb2+ (100 mg/L), Hg2+ (25 mg/L), and Zn2+ (50 mg/L). The genes responsible for chemotaxis (cheA, cheB, cheR, cheV, and cheY), which are also crucial for adhesion, were identified and silenced via RNAi. We observed that a decrease in chemotactic gene expression reduced the ability of the organism to demonstrate adhesion, motility, chemotaxis, and biofilm formation. Upon comparing the cheY-RNAi bacteria to the wild-type strain, we observed that the transcriptome of V. harveyi was significantly altered. Additionally, the expression of key genes and the adhesion ability were affected by the pH (pH of 5, 6, 7, 8, and 9), salinity (NaCl at concentrations of 0.8%, 1.5%, 2.5%, 3.5%, or 4.5%), and temperature (4, 15, 28, 37, and 44 °C) of the medium. Based on these results, the following conclusions were made: (1) The chemotactic genes cheA, cheB, cheR, cheV, and cheY may regulate the adhesion ability of V. harveyi by affecting bacterial motility, and participate in the regulation of adhesion at different temperatures, salinities and pH values; (2) stable silencing of cheA could alter the transcriptional landscape of V. harveyi and regulate the expression of genes associated with its adhesion mechanisms.